2017
DOI: 10.1111/bcp.13193
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant in pediatric patients using moderate and highly emetogenic protocols: a systematic review and meta‐analyses of randomized controlled trials

Abstract: Triple therapy decreased CIV risk, without increasing the occurrence of febrile neutropenia. However, this review could not address which subpopulations would most benefit from using this strategy. Future studies should focus on assessing risk factors for nausea and vomiting, as many patients did not achieve a complete antiemetic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
4
1
1
Order By: Relevance
“…Clinical drug-related side effects were similarly low in both groups. New or different safety issues were not observed in this study compared with previous studies with fosaprepitant in adult and pediatric patients [3, 4, 7, 12, 13].…”
Section: Discussioncontrasting
confidence: 64%
“…Clinical drug-related side effects were similarly low in both groups. New or different safety issues were not observed in this study compared with previous studies with fosaprepitant in adult and pediatric patients [3, 4, 7, 12, 13].…”
Section: Discussioncontrasting
confidence: 64%
“…Among the AEs, the incidence of febrile neutropenia seemed higher with fosaprepitant (17.5%–23.3% across doses; apparently not dose related) than with the control regimen (11.4%); however, these results should be interpreted cautiously because this study was not powered to determine differences in the rates of febrile neutropenia between treatment groups. Although there are reports of increased incidence of febrile neutropenia with combination standard antiemetic therapy and NK 1 RA relative to standard antiemesis alone (conducted in either adult or adolescent patients), the majority of placebo‐controlled studies have found no significant difference in the rate of febrile neutropenia between antiemesis regimens with and without NK 1 RA, irrespective of patient age . Rates of neutropenia and pyrexia, also indications of infection, were similar between fosaprepitant and the control regimen (neutropenia: 20.0%–25.6% vs 25.7%; pyrexia: 7.0%–11.9% vs 11.4%).…”
Section: Discussionmentioning
confidence: 98%
“…32 New or different, potential, fosaprepitant-related adverse events, as described in previous studies, were not observed. 15,16,28,35 Since this study was conducted in a non-randomized, observational setup, the conclusions that can be drawn are limited. Due to inconsistencies in the chart documentation and the difficulties with younger pediatric patients (under 4 years of age) reporting nausea, a valid assessment of nausea was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Randomized clinical trials have proven the safety and good efficacy of a CINV prophylaxis regimen with aprepitant or fosaprepitant for adult and pediatric patients after emetogenic chemotherapy, during both the acute and delayed CINV phases. 13,15,16 However, there is few data on pediatric patients receiving an antiemetic prophylaxis with fosaprepitant during moderately or highly emetogenic chemotherapy. 11,16,17 Based on fosaprepitant's favorable properties, in terms of safety and efficacy, for adult patients and those of oral aprepitant in pediatric patients, the standard CINV prophylaxis regimen used for pediatric patients receiving moderately or highly emetogenic chemotherapy in the University Children's Hospital Tübingen was gradually changed from a regimen of granisetron with or without dexamethasone, to a prophylaxis regimen with additional single-dose intravenous fosaprepitant directly before the first administration in the respective chemotherapy course of a moderately or highly emetogenic chemotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%